The Use of HPTLC and SDS-PAGE Methods for Coniferous Honeydew Honey Fingerprinting Compiled with Mineral Content and Antioxidant Activity - Monika Tomczyk; Aleksandra Bocian; Ewelina Sidor; Michał Miłek; Grzegorz Zaguła; Małgorzata Dżugan (Molecules, 2022)
Fir honeydew honey is a uniquely beneficial product which is often subjected to adulteration; however, pollen analysis is not useful to verify this honey type. Fourteen samples of EU protected designation of origin fir honeydew honey gathered directly from apiaries were studied. Standards of legal requirements and additional parameters, i.e., specific optical rotation, mineral content, and antioxidant activity, were tested. Five nectar honeys of different varieties were used as a comparative material. HPTLC and SDS-PAGE methods were used to fingerprint the honey types. All honeys tested fulfilled the quality requirements in terms of water content, pH, total acidity, conductivity, HMF, and diastase number. They were defined as dark amber on the Pfund scale and exhibited positive specific rotation (+2.5 to 25). Honeydew honey surpassed the tested nectar honeys in terms of mineral content and antioxidant activity as well as total polyphenolic content, except for buckwheat honey. The sugar and polyphenolic profile obtained by HPTLC allowed to distinguish honeydew from nectar honeys. The same was achieved by SDS-PAGE protein profiling. Both techniques seem to be cheap and quick tools for precisely distinguishing honeydew honey.